If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8y + 9)(8y + -9) = 0 Reorder the terms: (9 + 8y)(8y + -9) = 0 Reorder the terms: (9 + 8y)(-9 + 8y) = 0 Multiply (9 + 8y) * (-9 + 8y) (9(-9 + 8y) + 8y * (-9 + 8y)) = 0 ((-9 * 9 + 8y * 9) + 8y * (-9 + 8y)) = 0 ((-81 + 72y) + 8y * (-9 + 8y)) = 0 (-81 + 72y + (-9 * 8y + 8y * 8y)) = 0 (-81 + 72y + (-72y + 64y2)) = 0 Combine like terms: 72y + -72y = 0 (-81 + 0 + 64y2) = 0 (-81 + 64y2) = 0 Solving -81 + 64y2 = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '81' to each side of the equation. -81 + 81 + 64y2 = 0 + 81 Combine like terms: -81 + 81 = 0 0 + 64y2 = 0 + 81 64y2 = 0 + 81 Combine like terms: 0 + 81 = 81 64y2 = 81 Divide each side by '64'. y2 = 1.265625 Simplifying y2 = 1.265625 Take the square root of each side: y = {-1.125, 1.125}
| -3.128*7000000= | | 156-4x=32x+16 | | 17-7x=132-28x | | 215-2x=43x+20 | | 3-x=2x-3 | | 9x-7=5(2x-4) | | 6x-7=73-10x | | -10x-2x=14-8x | | 2(a+3)+3(a-1)= | | -3(4x+1)+3= | | 12.6x+5.8=9x-4.3 | | 4x+7=107-4x | | 8+(x-3)=19 | | 5x+7x=39 | | -19-2x=13-2x | | 8+(x+3)=19 | | 66-3x=42x-16 | | 59-3x=33x+15 | | x*6+126=11-14 | | t^2-9t-10=0 | | X=37.56+0.25x | | C=37.56+0.25x | | 12.6+5.8=9x-4.3 | | (-2)-3y=-6 | | 34a-4(5a+2)=32 | | 93-3x=33x+17 | | 14-7x=24-14x | | 5x^2+8x-2=0 | | 3n+3=2n+3 | | 11x-111=6x-11 | | 14-10x=174-38x | | 146-3x=42x+16 |